2015
DOI: 10.1007/s10886-015-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Blend Analysis and Cross-Attraction among Populations of Maruca vitrata from Asia and West Africa

Abstract: The legume pod borer, Maruca vitrata, is a pantropical pest on leguminous crops. (E,E)-10,12-Hexadecadienal, (E,E)-10,12-hexadecadienol, and (E)-10-hexadecenal were described previously as sex pheromone components for this nocturnal moth. A blend of these components in a ratio of 100:5:5 attracted males in field trapping experiments in Benin, but not in Taiwan, Thailand, or Vietnam. This finding suggests geographic variation in the pheromone blend between Asian and West African populations of M. vitrata. We, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…These variations could have been caused by various natural factors, including food (Groot et al ., ), age, mating status, and environmental conditions such as photoperiod, temperature (Ono, ; Ding et al ., ) and the use of pesticides (Trimble et al ., ; Wei et al ., ; Shen et al ., ), which are factors with known effects on the female sex pheromone biosynthesis pathway. Accordingly, conspecific males adapt to these biotic and abiotic factors (Jarriault et al ., ; Groot et al ., ; Barrozo et al ., ; Deisig et al ., ; Rabhi et al ., ; Schlager et al ., ), which leads to the modulation of odour‐driven behaviour through the concerted regulation of odour maps (Saveer et al ., ). Our field bioassays of the sites where the female moths were collected demonstrated this olfactory plasticity, as the optimal blend that attracted the male moths varied amongst the geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…These variations could have been caused by various natural factors, including food (Groot et al ., ), age, mating status, and environmental conditions such as photoperiod, temperature (Ono, ; Ding et al ., ) and the use of pesticides (Trimble et al ., ; Wei et al ., ; Shen et al ., ), which are factors with known effects on the female sex pheromone biosynthesis pathway. Accordingly, conspecific males adapt to these biotic and abiotic factors (Jarriault et al ., ; Groot et al ., ; Barrozo et al ., ; Deisig et al ., ; Rabhi et al ., ; Schlager et al ., ), which leads to the modulation of odour‐driven behaviour through the concerted regulation of odour maps (Saveer et al ., ). Our field bioassays of the sites where the female moths were collected demonstrated this olfactory plasticity, as the optimal blend that attracted the male moths varied amongst the geographical regions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found only two pheromone compounds in M. vitrata populations from Taiwan, Thailand, Vietnam, and Benin (Schläger et al, 2015). A recent study found only two pheromone compounds in M. vitrata populations from Taiwan, Thailand, Vietnam, and Benin (Schläger et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Damage to stems, peduncles, flowers and pods leads to significant yield losses of legume species (Chang & Ramasamy ; Patel & Singh ; Schläger et al . ; Singh & Allen ). The grain yield loss due to M. vitrata is estimated to be 10% to 80% in various crops (Sharma ; Singh & Allen ).…”
Section: Introductionmentioning
confidence: 99%